Livingston family papers - Livingston, Edward, 1764-1836.; Livingston, Robert R., 1746-1813.; Livingston, William, 1723-1790.
Correspondence, act, resolution, indentures, land title, and other papers pertaining to U.S. national politics, French political and economic conditions, and financial and legal matters of the Livingston family. Topics include the Continental Congress and army, war with Great Britain, a conspiracy to assassinate George Washington, and the leadership of Napoleon Bonaparte. Correspondents include William P. Farrand, John Jay, and Gouverneur Morris.
In part, positive and negative photocopies and typewritten transcripts.
Robert R. Livingston, lawyer, delegate to the U.S. Continental Congress from N. Y., cabinet officer, and diplomat; Edward Livingston, lawyer, U.S. representative from N.Y., mayor of New York (city), U.S. representative and senator from Louisiana, cabinet officer, and diplomat; William Livingston, lawyer, delegate to the U.S. Continental Congress from New Jersey, and governor and public official of New Jersey; and other members of the Livingston family.
Keywords: Farrand, William P. -- 1777-1839 -- Correspondence; Jay, John, -- 1745-1829 -- Correspondence; Morris, Gouverneur, -- 1752-1816 -- Correspondence; Napoleon -- I, -- Emperor of the French, -- 1769-1821.; Washington, George, -- 1732-1799.; Livingston family; United States. -- Continental Congress; United States. -- Continental Army; France -- Economic conditions; France -- Politics and government; United States -- History -- Revolution, 1775-1783.; United States -- Politics and government